Question:
Fernando evaluated the expression below.
![\frac{5(9-5)}{2} + (-2)(-5) + (-3)^2 = \frac{5(4)}{2} -10 + 9 = \frac{20}{2} - 10 + 9 = 10 - 10 + 9 = 9](https://tex.z-dn.net/?f=%5Cfrac%7B5%289-5%29%7D%7B2%7D%20%2B%20%28-2%29%28-5%29%20%2B%20%28-3%29%5E2%20%3D%20%5Cfrac%7B5%284%29%7D%7B2%7D%20-10%20%2B%209%20%3D%20%5Cfrac%7B20%7D%7B2%7D%20-%2010%20%2B%209%20%3D%2010%20-%2010%20%2B%209%20%3D%209)
What was Fernando's error?
- Fernando evaluated the numerator of the fraction incorrectly.
- Fernando simplified 20/2 incorrectly.
- Fernando incorrectly found the product of –2 and –5.
- Fernando evaluated (-3)² incorrectly.
Answer:
- Fernando incorrectly found the product of –2 and –5.
Explanation:
Given
![\frac{5(9-5)}{2} + (-2)(-5) + (-3)^2 = \frac{5(4)}{2} -10 + 9 = \frac{20}{2} - 10 + 9 = 10 - 10 + 9 = 9](https://tex.z-dn.net/?f=%5Cfrac%7B5%289-5%29%7D%7B2%7D%20%2B%20%28-2%29%28-5%29%20%2B%20%28-3%29%5E2%20%3D%20%5Cfrac%7B5%284%29%7D%7B2%7D%20-10%20%2B%209%20%3D%20%5Cfrac%7B20%7D%7B2%7D%20-%2010%20%2B%209%20%3D%2010%20-%2010%20%2B%209%20%3D%209)
Required
Spot the error
The error in this evaluation is the product of -2 and -5 at step 2
When a negative number (-2) is multiplied by a negative number (-5), the outcome of the multiplication is always a positive number (10).
So, the result of -2 * -5 is 10 but Fernando incorrectly calculated it as -10.
Solving the expression, correctly
![\frac{5(9-5)}{2} + (-2)(-5) + (-3)^2 = \frac{5(4)}{2} + 10 + 9](https://tex.z-dn.net/?f=%5Cfrac%7B5%289-5%29%7D%7B2%7D%20%2B%20%28-2%29%28-5%29%20%2B%20%28-3%29%5E2%20%3D%20%5Cfrac%7B5%284%29%7D%7B2%7D%20%2B%2010%20%2B%209)
![\frac{5(9-5)}{2} + (-2)(-5) + (-3)^2 = \frac{20}{2} + 10 + 9](https://tex.z-dn.net/?f=%5Cfrac%7B5%289-5%29%7D%7B2%7D%20%2B%20%28-2%29%28-5%29%20%2B%20%28-3%29%5E2%20%3D%20%5Cfrac%7B20%7D%7B2%7D%20%2B%2010%20%2B%209)
![\frac{5(9-5)}{2} + (-2)(-5) + (-3)^2 = 10 + 10 + 9](https://tex.z-dn.net/?f=%5Cfrac%7B5%289-5%29%7D%7B2%7D%20%2B%20%28-2%29%28-5%29%20%2B%20%28-3%29%5E2%20%3D%2010%20%2B%2010%20%2B%209)
![\frac{5(9-5)}{2} + (-2)(-5) + (-3)^2 = 29](https://tex.z-dn.net/?f=%5Cfrac%7B5%289-5%29%7D%7B2%7D%20%2B%20%28-2%29%28-5%29%20%2B%20%28-3%29%5E2%20%3D%2029)
Hence, the actual result of the expression is 29 (not 9 as calculated by Fernando).